A new species of Trimma (Pisces; Gobiidae) from the Western Pacific Ocean - Winterbottom, Richard; Erdmann, Mark V. (Zootaxa, 2019)
A new species of Trimma, T. wangunui, is described from three localities in the western Pacific (Papua New Guinea, Timor-Leste and the Philippines). It belongs to a small group of species with scales in the predorsal midline, no scales on the cheek or the opercle, all pectoral fin rays unbranched, and a branched fifth pelvic fin ray. It differs from other species in this group in having an elongate second spine of the first dorsal fin which reaches to the bases of the 2nd–8th second dorsal-fin rays when adpressed, in having yellow bars on the head, and in the presence of vertically elongate yellow spots on a brown body when freshly collected.